Reconciling Ambiguity (tashkīk) and Superaddition (ziyāda) in Commentaries on Ṭusī’s Tajrīd al-iʿ tiqād: Iṣfahānī, Jurjānī, and Qushjī on Proper Existences (wujādat khāṣṣa) - Zachary Candy (Nazariyat: Journal for the History of Islamic Philosophy and Sciences)
The ontology of the Necessary Existent was a topic of heated controversy in the twelfth to thirteenth centuries: Fakhr al-Dīn al-Rāzī argued that existence is superadded to (zā’id ʿalā) all essences, including the Neces- sary Existent’s, while Naṣīr al-Dīn al-Ṭūsī used the notion of existence’s ambiguous predication (tashkīk al-wujūd) to argue for the identity of the Necessary’s essence with its existence. This paper analyzes the synthesis of Rāzīan superaddition and Ṭūsīan ambiguity as developed in early commentaries on Ṭūsī’s Tajrīd al-iʿtiqād, namely the Tas- dīd al-qawāʿid of Shams al-Dīn al-Iṣfahānī (d. 1348) with its glosses by al-Sayyid al-Sharīf al-Jurjānī (d. 1414), and the “new” commentary by ʿAlāʾ al-Dīn al-Qūshjī (d. 1474). After surveying the development of the new synthesis, which entails “three tiers” (thalātha umūr) of unqualified existence (wujūd muṭlaq), proper existence (wujūd khāṣṣ), and quiddity (māhiyya), I highlight Qūshjī’s suggestion, in response to Iṣfahānī’s argument (and Jurjānī’s denial) that ambiguity entails superaddition, that these proper existences are metaphysically superfluous. Qūshjī thus proposes a sparser ontology comprising only unqualified existence and quiddity but still making good on his predecessors’ concerns: I examine his arguments in his subsequent discussions of existence’s diversification among existents and, finally, of existence’s superaddition to the Necessary.